Vigilância em saúde da população exposta aos agrotóxicos pela ótica das organizações de Campo Verde – MT - Onishi, Clarissa Ayumi (2014)
This is a study of contextualized questioning about agribusiness agriculture that exposes the population to varying degrees to the effects of pesticides and governmental regulation. The research sought to grasp the perspective of formal organizations through interviews with representatives of associations, unions of producers, rural entrepreneurs, workers union and the city government on health and environment sector, opinion / position on environmental exposure to pesticides and the consequences human health. The premise of the research was that part of the population exposure (intentional - linked to the agricultural mode of production) is the main determinant of economic growth and agricultural production as problematic in Campo Verde - MT, using agrochemicals, causing environmental contamination and effects on human health. Documentary research was carried out in relation to federal, state and local regulations on Health Surveillance, Health Surveillance and Worker Population Exposed to Pesticides, plus state environmental protection laws Health. Fifteen representatives of formal organizations were selected for interview, four segment of farmers; three of the local community (residents association, workers union), eight local government representatives (five in the municipal health department, two of the secretary of agriculture development and the environment, and the INDEA). We sought to learn how the representatives perceive related to agricultural production in the county impacts, which are the actions of health surveillance and environmental monitoring; suggestions and strategic measures; difficulties in implementing this specific surveillance. Farmers do not believe that local agriculture can harm the health, blaming the worker if intoxicate and find unnecessary deployment of surveillance; workers recognize the risks of pesticide exposure, omit ahead to the economic and financial dependence provided by agribusiness, and local government, although important to find this kind of surveillance, accommodates itself to the interests of agribusiness as difficulty deployment of surveillance.